Pengaruh Jumlah Tanggungan Keluarga Dan Pendidikan Terhadap Kemiskinan - Endang Budi Sri Rahayu; Usman Moonti; Ardiansyah Ardiansyah; Maya Novrita Dama; Imam Prawiranegara Gani; Yulianti Toralawe (Universitas Negeri Gorontalo, 2022)
This study aims to determine the influence of number of family dependents and education on poverty of the village communities in Sari Murni Village, Randangan Sub-Distric, Pohuwato Regency. The method used in this study is a quantitative method. The respondes amounted to 34 people in Sari Murni Village, Randangan Sub-Distric, Pohuwato Regency. The main instrument used was questionnaires. The collected data were analyzed by linear regression and continued to be carried out with the classical assumption test. Data collection techniques were carried out through observation, interviews, questionnaires, and documentation. The population and samples were selected from a total of 34 low-income families with less than four family dependents (4) in Sari Murni Village, Randangan Sub-Distric, Pohuwato Regency. The result of the variability regardine poverty and education in Sari Murni Village, Randangan Sub-Distric, Pohuwato Regency indicated that the number of family dependens and education simultaneously affect poverty.